Epigenetic regulation of human embryonic stem cells - Hu, Qidong; Rosenfeld, Michael G. (Frontiers in Genetics, 2012)
Recently, there has been tremendous progress in characterizing the transcriptional network regulating hESCs (MacArthur et al., 2009; Loh et al., 2011), including those signaling events mediated by Oct4, Nanog and Sox2. There is growing interest in the epigenetic machinery involved in hESC self-renewal and differentiation. In general, epigenetic regulation includeschromatin reorganization, DNA modification and histone modification, which are not directly related to alterations in DNA sequences. Various protein complexes, includingPolycomb, trithorax, NuRD, SWI/SNF andOct4, have been shown to play critical roles in epigenetic control of hESC maintenance and differentiation. Hence, we will formally review recent advances in unraveling the multifaceted role of epigenetic regulation in hESC self-renewal and induced differentiation, particularly with respect to chromatin remodeling and DNA methylation events. Unraveling the molecular mechanisms underlying the maintenance/differentiation of hESCs and reprogramming of somatic cells will greatly strengthen our capacity to generate various types of cells to treat human diseases.